The centrality of didactics in teacher education and the contributions of sensitive didactics - d'Ávila, Cristina (2025)
The article aims to analyse the centrality of Sensitive Didactics in teacher formation through the Didactic Atelier device, to discuss the role of General Didactics and specific didactics in teacher formation, addressing the repercussions of their devaluation in curricula and education, and to highlight the contribution of Sensitive Didactics to university teacher formation through the resignifications promoted by the experience of Didactic Ateliers.The motivation for his writing comes from the verification of the role that has been subsumed by the specific Didactics. Despite of the fact that Didactics is central to teacher education, this scientific discipline has been made invisible, if not disappeared from the curricula of undergraduate courses. In this interregnum, it is interesting to bring the contributions of Sensitive Didactics to teacher education, an innovative approach, based on the assumption of the integrality of the constitution of human beings (body-mind-emotions) that needs to be mobilized and respected in educational spaces, whether in basic or higher education. For the article in question, we bring up the example of the Didactic Ateliers (AD), an educational device geared towards university professors, based on the sensitive Didactics. Methodologically, a research-formation was undertaken supported by an electronic survey, interpreted by thematic content analysis arranged in three categories: Sensitive Didactics, Teacher Education and Resignifications. It was deduced from the results of the research with teachers involved in AD, not only its innovative content, but also important resignifications about teacher education and the role of centrality of sensitive didactics in it.